Pug's road trip - May, Kyla (2022)
When their friend Jack cannot join them, Bub the pug and his human, Bella, vow to bring him souvenirs from their road trip, and despite some bumps along the way, Bub calls their trip a big success.
Keywords: Pug -- Juvenile fiction; Squirrels -- Juvenile fiction; Human-animal relationships -- Juvenile fiction; Voyages and travels -- Juvenile fiction; Theft -- Juvenile fiction; Diaries -- Juvenile fiction; Pug -- Fiction; Dogs -- Fiction; Squirrels -- Fiction; Human-animal relationships -- Fiction; Voyages and travels -- Fiction; Diaries -- Fiction; Diary fiction